Implementation of Customary Law in Land Dispute Resolution in Indigenous Law Communities - Adila, Arina; Alexandra, Sallie (LPPM Universitas Sains dan Teknologi Komputer, 2025)
Land disputes within indigenous law communities remain a complex and evolving issue in Indonesia. Although customary law is recognized within the national legal framework, its implementation continues to face various challenges, including limited formal recognition and overlapping agrarian regulations. This study aims to analyze the effectiveness of customary law in resolving land disputes, compare it with national litigation mechanisms, and identify factors influencing its application. Employing both empirical and normative legal approaches, this research utilizes in-depth interviews, observations, and legal document analysis. The study sample includes customary leaders, agrarian officials, law enforcement officers, and disputing community members. Findings indicate that 75% of the 100 land dispute cases examined were successfully resolved through customary mechanisms, whereas only 30% of cases reached resolution through national litigation. Additionally, the average time required for dispute resolution under customary law was approximately four months, significantly shorter than the three to five years typically needed for litigation. Key factors supporting the effectiveness of customary law include the flexibility of deliberative mechanisms, high community compliance, and a restorative justice approach. However, the implementation of customary law still faces challenges regarding legal legitimacy, external interventions, and the lack of regulatory support to accommodate indigenous dispute resolution mechanisms. Therefore, more inclusive policies are needed to integrate customary law into the national legal system, creating a more effective and equitable dispute resolution framework